REPARACION DE UN MOTOR DE COMBUSTION INTERNA 1.3 FIRE - BARROS BERMEO, HUGO OSWALDO (2014)
This paper details the procedure that was performed for the development of the REPAIR OF AN INTERNAL COMBUSTION ENGINE FIRE 1.3. The project aims to identify and resolve the underlying causes low compression pistons 2 and 3 by the knowledge acquired in our institution Protmec, it is worth noting that the achievement of our graduation project conducted due consultations of the teaching material obtained in process studies and tools provided by our institute which was fundamental to the development and implementation of the proposed objective piece. Besides solving the problem of low compression pistons present in 2 and 3, we couple a catalyst to meet the standards required to exhaust regulators transit in our country, achieving comply with our society and the environment.